THE ROLE OF GUIDANCE AND COUNSELING TEACHERS TO OPTIMIZE SOCIAL CONSTRUCTIVISM IN LEARNING AT SCHOOL - Alvin Nayandra M Perangin Angin; Desta Alfia; Ila Halimah; Kinanti Oktafiani; Risma Nursyani (Psikoeduko: Jurnal Psikologi Edukasi dan Konseling, 2023)
Social constructivism in learning is a form of educational theory that prioritizes increasing the logical and conceptual development of learners. What makes the problem is that students who construct their knowledge, not infrequently that the results of student construction do not match the results of the construction of scientists, causing misconceptions. This article is an analysis of the situation using qualitative methods. Qualitative methods are research whose preparation uses data collection techniques by conducting interviews and observations for collection. In addition, supporters are reading, recording, and reviewing data from journals and articles from electronic media and books related to "The Role of Guidance and Counseling Teachers to Optimize Social Constructivity in Learning in Schools". Based on the results of the study, efforts were obtained to optimize educators for social constructivist methods in learning students with the role of Guidance and Counseling teachers, must know in advance the disadvantages and advantages to avoid misconceptions, constructivism can be an approach to the implementation of guidance and counseling that occurs in schools. Counseling with constructivism is not like traditional things that see something from the individual but focus more on the strengths of students, leading to positive traits such as paying attention to resources, dreams of counselors, hopes, goals, and potentials possessed by counselors. In this constructivist counseling approach, getting meaning is not always from the individual himself, it can also be from his social relationships.